Factores asociados a la sintomatología depresiva en estudiantes de medicina de la Universidad Nacional de Trujillo - Rojas Castrejón, Patricia Irene (2019)
Objective: To determine the associated factors, prevalence and levels of depressive symptomatology in medical students of the National University of Trujillo (UNT). Material and method: Descriptive and cross-sectional study, with 502 students of the Faculty of Medicine of the UNT - 2018, prevalence was calculated, levels were assessed and the association between categorical variables was determined by Pearson's Chi-square test (p <0.05). Results: From 502 validated surveys it was obtained that 33.1% (95% CI: 30.82 - 38.12) of students presented depressive symptomatology; with a predominance of the mild level (31.3%), moderate level (1.6%) and severe level (0.2%). Associated factors are: Sociodemographic factors: female sex (p = 0.000), live alone (p = 0.004), work (p = 0.003); academic factors: preclinical academic years (p = 0.000), failed course (p = 0.00) ; Habitats factors: short time for recreation (p = 0.000) and alcohol drinking habit (p = 0.013). Conclusions: The prevalence of depressive symptomatology is 33.1%, the mild level is the most prevalent and the factors associated with it are : female sex, live alone, work, preclinical academic years, failed course, little time for recreation and habit of drinking alcohol.